PERANAN SANREGO (Lunasia amara Blanco) DALAM PENINGKATAN LIBIDO SEKSUAL RUSA TIMOR (Cervus timorensis de Blainville, 1822) JANTAN [The Role of Sanrego (Lunasia amara Blanco) to Increasing Libido Sexual of Male Timor Deer (Cervus timorensis de Blainville) - . Zumrotun; Burhanuddin Masyud; A. Machmud Thohari (Media Konservasi, 2006)
This research was carried out to know the role of sanrego and the dosage responses of sanrego to increase libido sexual of male timor deer. Four sanrego levels (0, 600, 800 and 1000 mg/head/day) were tested to a total of 12 male timor deers using completely random design with three replication for each treatment. Some parameters of libido sexual dan behaviour were observed i.e. approach female, smelling of vulva, crying stage, wallow in a mudhole, scrub its velvet, agonistic and mounting female shoulder. Result of research showed that the role of sanrego was significant (P< 0.05) to increase libido sexual of male timor deer. Dosage of 10.000 mg/head/day showed improvement of sexual activities. However research result significantly not yet stimulate the male deer to copulate female deer.Key words : libodo sexual, mating behaviour, male timor deer, sanrego, hormone